TANTANGAN DAN PELUANG: ANALISIS DAMPAK BOIKOT TERHADAP KINERJA SAHAM PERUSAHAAN YANG TERLIBAT KONTROVERSI ISU ISRAEL - Novanti, Hani (Gapenas Publisher, 2023)
This study aims to analyze the impact of the boycott on the stock prices of companies that allegedly support Israel in the context of the Israeli-Palestinian conflict. Through the collection and analysis of stock closing price data during 2023 from five selected companies, namely Unilever Indonesia, PT. Mitra Adiperkasa, PT MAP Boga Adiperkasa, PT Fast Food Indonesia Tbk, and PT Metrodata Electronics Tbk, and using a t-test paired sample, this study evaluates whether there is a difference in stock prices between the previous quarter (quarter 1-3) and the quarter affected by the boycott (quarter 4). The results of the analysis show that although there is an average difference in stock prices between the two periods, the difference is not statistically significant. The high correlation between stock prices in both periods shows that there is consistency in the trend of stock price movements. Thus, the results of this study provide valuable insights into understanding the impact of the boycott on the stock prices of companies that allegedly support Israel